Unlocking opportunities for climate action toward net zero requires a blue transition - Hossain, Peerzadi Rumana (WorldFish, 2022)
The blog post tackled the importance of setting up a climate adaptation pathway map for climate-resilient aquatic food systems. It elaborated on how aquatic food systems can lead the way to mitigation if urgent blue climate actions to combat climate crisis are taken into account.